2007
DOI: 10.1111/j.1348-0421.2007.tb03918.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inhibitory Capacity of an Anti‐C5a Complementary Peptide Following Acetylation of N‐terminal Alanine

Abstract: Amino acids 37 to 53 (RAARISLGPRCIKAFTE) of C5a anaphylatoxin form an essential region for C5a function. To target this sequence, we generated a complementary peptide (ASGAPAPGPAGPLRPMF) designated PepA which has a potent inhibitory effect on C5a activity. By introducing an acetyl group at the N‐terminal alanine of PepA, an acetylated form was generated which was designated AcPepA. The acetylation resulted in increased inhibition of C5a stimulation of neutrophils as determined by Ca influx. Furthermore, AcPepA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…As a result, it was considered that further complement activation might be suppressed and that C3b deposi- tion was decreased; therefore, we considered that C5a might be a target of therapeutic approaches for peritoneal injury. In the present study, we used a complementary small peptide, AcPepA, previously reported to prevent the role of C5a (30). AcPepA was also reported to be a powerful C5a inhibitor capable of blocking C5a in septic monkeys (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, it was considered that further complement activation might be suppressed and that C3b deposi- tion was decreased; therefore, we considered that C5a might be a target of therapeutic approaches for peritoneal injury. In the present study, we used a complementary small peptide, AcPepA, previously reported to prevent the role of C5a (30). AcPepA was also reported to be a powerful C5a inhibitor capable of blocking C5a in septic monkeys (29).…”
Section: Discussionmentioning
confidence: 99%
“…FITC-labeled polyclonal goat anti-rat C3b was purchased from Cappel (Solon, OH). AcPepA was generated according to our previous report (30). A C5aR antagonist (C5aRA) hexapeptide, NMePhe-Lys-Pro-dCha-Trp-dArg (synthesized by the Peptide Institute, Osaka, Japan) was originally reported by Konteatis et al (15) and has been confirmed to inhibit C5a activation in animal models (14,27).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…We generated an inhibitory peptide of C5a composed of an amino acid sequence ASGAPAPGPAGPLRPMF named PepA [3]. Acetylation at the N-terminal alanine of PepA improved the C5a inhibitory capacity and was named AcPepA [4].…”
Section: Introductionmentioning
confidence: 99%